Energy Islands : metaphors of power, extractivism, and justice in Puerto Rico - De Onis, Catalina M., 1986- (Environmental communication, power, and culture, 2021)
"Energy Islands provides an urgent and nuanced portrait of collective action that resists racial capitalism, colonialism, and climate disruption. Weaving together historical and ethnographic research, Catalina M. de Onís challenges the master narratives of Puerto Rico as a tourist destination and site of "natural" disasters. She demonstrates how fossil-fuel economies are inextricably entwined with colonial practices and policies and how local community groups in Puerto Rico have struggled against energy coloniality and energy privilege to mobilize and transform power from the ground up. This work decenters continental contexts and deconstructs damaging hierarchies that devalue and exploit disenfranchised rural, coastal communities. Onís highlights and collaborates with individuals who refuse the cruel logics and discourses of empire and domination by imagining and implementing energy justice and other interconnected radical power transformations. Diving deeply into the concepts of energy, islands, and power, this book engages various metaphors for alternative world-making"--